2017
DOI: 10.1080/21580103.2017.1387611
|View full text |Cite
|
Sign up to set email alerts
|

Soil hydrophysical degradation associated with forest operations

Abstract: Skid trails in the Hyrcanian forest of northern Iran are important for moving wood to log landings; however, they can cause soil compaction and alter water infiltration. This research therefore presents an analysis of the impact of ground-based skidding on soil hydrophysical properties in Kuhmiyan forest located in the Hyrcanian forest. Soil infiltration, bulk density, and soil resistance to penetration have been studied at three different depths of soil along the skid trails. Three sampling locations were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Ground-based extraction activities and skid trail construction result in structural changes to and compaction of soils, which is immediately evident in measurements of parameters such as bulk density, porosity (Ares et al, 2005;Curran et al, 2007;Han et al, 2009;Arthur et al, 2013;Solgi and Najafi, 2014;Cambi et al, 2016a, b;Marchi et al, 2016;Cambi et al, 2017) and K sat (Ziegler et al, 2006;Curran et al, 2007;Rej sek et al, 2011;Arthur et al, 2013;Abdi et al, 2017). Generally, steel-tracked small shovel loaders and rubber-tracked carriers are the most frequently used machinery in logging operations in Korea.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ground-based extraction activities and skid trail construction result in structural changes to and compaction of soils, which is immediately evident in measurements of parameters such as bulk density, porosity (Ares et al, 2005;Curran et al, 2007;Han et al, 2009;Arthur et al, 2013;Solgi and Najafi, 2014;Cambi et al, 2016a, b;Marchi et al, 2016;Cambi et al, 2017) and K sat (Ziegler et al, 2006;Curran et al, 2007;Rej sek et al, 2011;Arthur et al, 2013;Abdi et al, 2017). Generally, steel-tracked small shovel loaders and rubber-tracked carriers are the most frequently used machinery in logging operations in Korea.…”
Section: Discussionmentioning
confidence: 99%
“…Soil compaction may also indicate a considerable reduction in soil permeability. For example, Rej sek et al (2011) and Abdi et al (2017) reported that wheel contact areas contributed to lower rates of soil infiltration (which can reduce soil saturation) than in other zones, such as undisturbed regions and the center of trails (because the rutted zones of skid trails are regularly compacted by vehicle movement). During the GP test, the K sat values in BTs and STs were significantly lower than in UAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides bulk density, soil penetration resistance was the second most commonly used indicator of soil disturbances and relied on the use of either analog [77][78][79] or digital penetrometers [80,81] to collect data at different location points and various depths on the machine operating trails. Monitoring soil moisture content at the same time as recording soil penetration resistance is pivotal since the latter is highly influenced by moisture content present in the soil.…”
Section: Disturbance Indicatorsmentioning
confidence: 99%
“…Monitoring soil moisture content at the same time as recording soil penetration resistance is pivotal since the latter is highly influenced by moisture content present in the soil. Because soil bulk density is linked to porosity, water infiltration was also monitored in field studies performed by [77,82] using double-ring infiltrometers.…”
Section: Disturbance Indicatorsmentioning
confidence: 99%